The effect of single tree selection cutting on herbaceous diversity in mixed oriental beech forest (Case study: Nav-e Asalem, Guilan) - Zahra Moradi; Hasan Pourbabaei; Ali Salehi; Alireza Sayyadi (تحقیقات جنگل و صنوبر ایران, 2015)
Variations in forest vegetation are effected by several factors, one of the most important of which being the crown canopy. This study aims to survey the effect of close and open crown canopy on the herbaceous diversity in Nav-e Asalem forests in Guilan province. To this aim, 15 canopy gaps of small (100-200 m2), medium (200-300 m2) and large (300-400 m2) sizes were selected with 5 replications each. Moreover, control plots of the same sizes were selected under the tree canopy. Along small and large diagonals in each gap microplots of 2×2 m each were measured in a randomized systematic design. The percentage of herbaceous cover was estimated using Domin scale. To assess plant diversity in each plot, diversity indices of Simpson, Shannon-Wiener, Smith-Wilson Evenness Index and herbaceous richness were derived. Results showed that increasing the gaps area resulted in a significant increase of diversity and richness. Furthermore, no significant difference was observed between diversity and richness indices between small area gaps and control areas.